Camel rating analysis of Eastern Bank Limited BRAC Bank Limited and Bank Asia Limited - Alam, Md. Wasif (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2022.